Leishmania amazonensis-Induced cAMP Triggered by Adenosine A2B Receptor Is Important to Inhibit Dendritic Cell Activation and Evade Immune Response in Infected Mice - Figueiredo, Amanda Braga; Souza-Testasicca, Míriam Conceição; Mineo, Tiago Wilson Patriarca; Afonso, Luís Carlos Crocco (Frontiers in Immunology, 2017)
Differently from others Leishmania species, infection by the protozoan parasite Leishmania amazonensis is associated with a lack of antigen-specific T-cell responses. Dendritic cells (DC) are essential for the innate immune response and for directing the differentiation of T-helper lymphocytes. Previously, we showed that L. amazonensis infection impairs DC activation through the activation of adenosine A2B receptor, and here we evaluated the intracellular events triggered by this receptor in infected cells. To this aim, bone marrow-derived DC from C57BL/6J mice were infected with metacyclic promastigotes of L. amazonensis. Our results show, for the first time, that L. amazonensis increases the production of cAMP and the phosphorylation of ERK1/2 in infected DC by a mechanism dependent on the A2B receptor. Furthermore, L. amazonensis impairs CD40 expression and IL-12 production by DC and the inhibition of adenylate cyclase, PI3K and ERK1/2 prevent these effects. The increase of ERK1/2 phosphorylation and the inhibition of DC activation by L. amazonensis are independent of PKA. In addition, C57BL/6J mice were inoculated in the ears with metacyclic promastigotes, in the presence of PSB1115, an A2B receptor antagonist. PSB1115 treatment increases the percentage of CD40+ DC on ears and draining lymph nodes. Furthermore, this treatment reduces lesion size and tissue parasitism. Lymph node cells from treated mice produce higher levels of IFN-γ than control mice, without altering the production of IL-10. In conclusion, we suggest a new pathway used by the parasite (A2B receptor - cAMP - PI3K - ERK1/2) to suppress DC activation, which may contribute to the decrease of IFN-γ production following by the deficiency in immune response characteristic of L. amazonensis infection.